Healing of Radiation Dermatitis with Ozonated Aloe Vera Oil by Increasing PDGF and Epidermal Thickness in Sprague-Dawley Rats - Utami, Widoasti Putri; , Yan Wisnu Prajoko; Prihharsanti, Christina H.N.; Sadhana, Udadi; Susilaningsih, Neni; Restiwijaya, Maryam; Nur, Muhammad (Folia Medica Indonesiana, 2022)
Highlights: • This study demonstrated the effect of ozonated Aloe vera oil in the healing of radiation dermatitis wound. • Groups that received no treatment was compared with groups that received treatment using 2.5% hydrocortisone ointment and ozonated Aloe vera. • Ozonated Aloe vera oil improves the healing of radiation dermatitis wound by increasing PDGF expression and epidermal thickness. Abstract : The long-term use of corticosteroids as a standard treatment for skin disorders, such as radiation dermatitis, can cause many side effects. Alternatively, ozonated Aloe vera oil may replace corticosteroids due to its fewer side effects and benefits in wound healing process. Re-epithelialization and the formation of growth factors, such as platelet-derived growth factor (PDGF), play an important role in the healing of dermatitis wound. This study intended to demonstrate the effect of ozonated Aloe vera oil to improve the healing of radiation dermatitis wound by increasing PDGF expression and epidermal thickness. This study used a post-test only control group design. A sample of 36 Sprague-Dawley rats was divided into 6 groups (C1=without treatment, C2=2.5% hydrocortisone ointment, P1=pure Aloe vera (AV), P2=300 mg/mL ozonated Aloe vera (OAV), P3=600 mg/mL OAV, P4=1200 mg/mL OAV. The expression of PDGF was assessed using Allred scoring with immunohistochemical staining, whereas the epidermal thickness was assessed using hematoxylin and eosin (H&E) staining at 400x microscopic magnification. The PDGF expression and epidermal thickness between the control and the treatment groups showed significant differences using a Kruskal-Wallis test (P=0.001) and one-way ANOVA test (P<0.001). The groups that was given ozonated Aloe vera oil had higher average of PDGF expression and thicker epidermis than the other groups. The Spearman's correlation test showed a strong positive relationship (p<0.001 and r=0.709) between the two variables. In conclusion, ozonated Aloe vera oil improves healing of radiation dermatitis wound by increasing PDGF expression and epidermal thickness.